Involvement of ceramide biosynthesis in increased extracellular vesicle release in Pkd1 knock out cells - Carotti, Valentina; van der Wijst, Jenny; Verschuren, Eric H. J.; Rutten, Luco; Sommerdijk, Nico; Kaffa, Charlotte; Sommers, Vera; Rigalli, Juan P.; Hoenderop, Joost G. J. (Frontiers in Endocrinology, 2022)
Autosomal Dominant Polycystic Kidney Disease (ADPKD) is an inherited disorder characterized by the development of renal cysts, which frequently leads to renal failure. Hypertension and other cardiovascular symptoms contribute to the high morbidity and mortality of the disease. ADPKD is caused by mutations in the PKD1 gene or, less frequently, in the PKD2 gene. The disease onset and progression are highly variable between patients, whereby the underlying mechanisms are not fully elucidated. Recently, a role of extracellular vesicles (EVs) in the progression of ADPKD has been postulated. However, the mechanisms stimulating EV release in ADPKD have not been addressed and the participation of the distal nephron segments is still uninvestigated. Here, we studied the effect of Pkd1 deficiency on EV release in wild type and Pkd1-/- mDCT15 and mIMCD3 cells as models of the distal convoluted tubule (DCT) and inner medullary collecting duct (IMCD), respectively. By using nanoparticle tracking analysis, we observed a significant increase in EV release in Pkd1-/- mDCT15 and mIMCD3 cells, with respect to the wild type cells. The molecular mechanisms leading to the changes in EV release were further investigated in mDCT15 cells through RNA sequencing and qPCR studies. Specifically, we assessed the relevance of purinergic signaling and ceramide biosynthesis enzymes. Pkd1-/- mDCT15 cells showed a clear upregulation of P2rx7 expression compared to wild type cells. Depletion of extracellular ATP by apyrase (ecto-nucleotidase) inhibited EV release only in wild type cells, suggesting an exacerbated signaling of the extracellular ATP/P2X7 pathway in Pkd1-/- cells. In addition, we identified a significant up-regulation of the ceramide biosynthesis enzymes CerS6 and Smpd3 in Pkd1-/- cells. Altogether, our findings suggest the involvement of the DCT in the EV-mediated ADPKD progression and points to the induction of ceramide biosynthesis as an underlying molecular mechanism. Further studies should be performed to investigate whether CerS6 and Smpd3 can be used as biomarkers of ADPKD onset, progression or severity.